Clomiphene treatment may be effective in refractory episodic and chronic cluster headache - Maria Eduarda Nobre; Mario Fernando Prieto Peres; Pedro Ferreira Moreira Filho; Antonio José Leal (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To describe the evolution of 15 patients who were treated for difficult-to-control episodic and chronic cluster headaches with clomiphene. Methods Clomiphene treatment was used for seven chronic and eight episodic cluster headache patients. The chronic patients were refractory to the medication being used, and the episodic patients, in addition to being resistant to conventional medication, had longer cluster headache periods, exceeding the average time of previous cluster cycles. Our main analysis was of the time to pain-free, complete remission, and the length of pain-free time and complete remission. Results Clomiphene was used for 45-180 days. The average time to being pain-free was 15 days and cluster remission was up to 60 days. The average time between being pain-free until cluster remission was 26 days. Conclusions Clomiphene treatment was significantly efficient. It interrupted chronicity in all patients, suggesting the capability of changing the pattern of attacks. It proved to be safe and well tolerated.